2021
DOI: 10.1039/d1dt00774b
|View full text |Cite
|
Sign up to set email alerts
|

Size modulation of MIL-125 nanocrystals to promote the catalytic performance towards oxidative desulfurization

Abstract: The Ti-based metal-organic framework (Ti-MOF) MIL-125 with tunable crystalline size in the range of ca. 50 nm to 1500 nm was synthesized by coordination modulation method using trans-cinnamic acid (CA)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…The calculated specific surface area is 5.026 m 2 /g. The adsorption curve is depicted as a type IV curve confirming the presence of mesopores [50–52] . This mesopore formation confirmed with the pore size distribution curve shown in Figure 2B, which reveal the BJH pore size is 3.78 nm and pore volume is 0.045 cm 3 /g.…”
Section: Resultssupporting
confidence: 69%
“…The calculated specific surface area is 5.026 m 2 /g. The adsorption curve is depicted as a type IV curve confirming the presence of mesopores [50–52] . This mesopore formation confirmed with the pore size distribution curve shown in Figure 2B, which reveal the BJH pore size is 3.78 nm and pore volume is 0.045 cm 3 /g.…”
Section: Resultssupporting
confidence: 69%
“…[169] (2019 Elsevier), Ref. [170] (copyright 2021 The Royal Society of Chemistry), and Ref. [171] (copyright 2019 Wiley-VCH).…”
Section: Energy Storage and Conversionmentioning
confidence: 99%
“…The result revealed that the UiO-66 colloidal particles with the smallest size and more missing linkers exhibited the best performance (Figure 17d). Li et al [170] synthesized MIL-125 MOF particles with different sizes and investigated their catalytic activity on oxidative desulfurization reaction of dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT) (Figure 17e-h). It was found that 50 nm MIL-125 particles have higher catalytic performance than those micrometer-sized particles (Figure 17i,j), possibly because the nanosized MOF particles had a larger external surface area, resulting in more accessible active sites.…”
Section: Catalysismentioning
confidence: 99%
See 2 more Smart Citations